2013
DOI: 10.18632/oncotarget.1060
|View full text |Cite
|
Sign up to set email alerts
|

DNA damage-induced ubiquitylation of proteasome controls its proteolytic activity

Abstract: Stability of proteins is largely controlled by post-translational covalent modifications. Among those, ubiquitylation plays a central role as it marks the proteins for proteasome-dependent degradation. Proteolytic activities of proteasomes are critical for execution of various cellular processes, including DNA damage signaling and repair. However, very little is known about the regulation of proteasomal activity in cells during genotoxic stress. Here we investigated post-translational modifications of the 20S … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
48
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(51 citation statements)
references
References 58 publications
(58 reference statements)
3
48
0
Order By: Relevance
“…2A). In agreement with the previously published data we did not detect gross changes in the composition of proteasomes purified from cells treated or non-treated with DR, although several subunits exhibited abnormal mobility in the gel due to post-translational modifications [26]. To visualise the spectra of RNA associated with proteasomes from non-treated and DR-treated cells the proteasome-associated RNA (pa-RNA) was extracted from the respective proteasome preparations and was subsequently end-labelled with [5'-P 32 ] pCp in the presence of T4 RNA ligase (Fig.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…2A). In agreement with the previously published data we did not detect gross changes in the composition of proteasomes purified from cells treated or non-treated with DR, although several subunits exhibited abnormal mobility in the gel due to post-translational modifications [26]. To visualise the spectra of RNA associated with proteasomes from non-treated and DR-treated cells the proteasome-associated RNA (pa-RNA) was extracted from the respective proteasome preparations and was subsequently end-labelled with [5'-P 32 ] pCp in the presence of T4 RNA ligase (Fig.…”
Section: Resultssupporting
confidence: 93%
“…Subsequent studies have identified the alpha5 subunit of CP as the one possessing RNAse activity. The latter can be regulated by various post-translational modifications in response to different environmental cues [18, 26]. Finally, the work from our group indicates that proteasomes may be involved in regulation of alternative splicing [27].…”
Section: Introductionmentioning
confidence: 99%
“…1 and 2, this protein pattern is similar to that before described for the bursa of Fabricius, brain, and whole blood cells. Interestingly, a new spot appeared on the 2D gel with the same molecular weight as β5, but a bit less alkaline, which is maybe due to phosphorylation or acetylation (Moiseeva et al 2013) of the subunit. Taken together, it appears that stimulation of spleen cells with PMA/ionomycin, which induced lymphocyte proliferation, did not provide any evidence for the induction of immunoproteasomes.…”
Section: Immune Stimulation Of Chicken Spleen Cellsmentioning
confidence: 99%
“…23,36 The functional outcome of Set7/9-mediated methylation of p53 and E2F1 is diametrically opposite for these two proteins: methylation of p53 on K372 stabilises the protein by inducing its subsequent acetylation, 37 yet methylation of E2F1 on K185 17 on the contrary, interferes with acetylation, promotes its ubiquitylation and subsequent degradation via the 26S proteasome. 38,39 It has also been shown that, in addition to p53 and E2F1, Set7/9 affects other substrates via regulating their protein stability either positively (ERa) 10 or negatively (DNMT1, RelA). 40,41 In this study, we report a novel function for Set7/9 as a critical co-activator of E2F1-dependent transcription in response to DNA damage.…”
mentioning
confidence: 99%